Research Trends on Creativity in Science Learning: A Literature Study (2018-2023) - Naf’atuzzahrah Naf’atuzzahrah; Syarful Annam; Yusuf Sarkingobir (Research in Education, Technology, and Multiculture, 2024)
Abstract: Creativity is one of the skills that students must have as a requirement to face the challenges of 21st century learning. This research aims to identify and analyze research trends on creativity in science learning in the form of journal ranking classifications, author and country of origin classifications as well as classifications based on keywords. This research is a type of qualitative research. The data used in this research was obtained from documents indexed by Google Scholar from 2018-2023 using Publish or Perish and Dimension.ai. The data analysis method used is bibliometric analysis with the help of VOSviewer software. The results of the analysis obtained show that the trend of writing articles about creativity in science learning has increased significantly in 2020, decreased in 2021 and increased again in 2022. The types of publications carried out include articles contained in journals, chapters, books, monographs, proceedings and preprints. The journal that contains the most articles about the PjBL model in science learning is the Journal of Physics Conference Series with total publications of 560 articles and 2,193 citations.    Keywords: creativity, science learning.